Validation of a portuguese version of the situational motivation scale (SIMS) in academic contexts - Gamboa, Vitor (2018)
The Situational Motivation Scale (SIMS), seeks to evaluate the motivation experienced when carrying out a specific task. The purpose of this research was to validate a Portuguese-language version of the scale, using a sample of 409 students, by attempting to reproduce its factor structure. The reliability analysis revealed acceptable internal consistency indexes in all subscales. Construct validity was assessed through Confirmatory Factor Analysis. The contributions of the factors and index of goodness-of-fit demonstrated the need to eliminate two items, which seems to agree with the results in other validation studies. Overall, results revealed that the SIMS is composed of four consistent factors and attested its psychometric quality. The scale does seem to represent a self-report measure of situational intrinsic motivation, identified regulation, external regulation, and amotivation, and can be widely used for the assessment of this construct in Portuguese academic contexts.